Outcome of Elastic Intramedullary Nailing for the Treatment of Paediatric Femoral Shaft Fractures. (Journal of Pakistan Orthopaedic Association, 2019)
Objective: To demonstrate the rate of union after closed elastic intramedullary nail fixation of paediatric femoral shaft fractures.Methods: The design of our study was descriptive and was conducted from 15-04-2016 to 15-10-2016 at Sheikh Zayed Medical College/Hospital, Rahim Yar Khan. All patients fulfilling inclusion criteria who underwent femur elastic intramedullary nail insertion in retrograde fashion for the treatment of Paediatric femur fractures were enrolled in the study. Patients were in regularly followed un-till radiological union.Results: A total of 55 patients including 33 males and 22 females with mean age 6.5±1.65 years and mean weight 19.11±4.46 kg were included. Fracture union was seen in 47 (85.45%) patients. There was almost equal union in both male and females with p value of 0.88. Better union was seen in age group of 5 to 8 years with union in 26 out of 29 patients as compared to age group of 9-12 years(p=0.35) Union was better seen in patients with weight less than 20 kg and duration of fracture 5 days or less with p values of 0.06 and 0.45. Thirty (90.91%) out of 33 patients had union in simple fractures as compared to comminuted in 17 out of 22 with p values of 0.16 as displayed.Conclusion: Elastic intramedullary nailing results in early union of femur shaft fractures in children with simple fractures who presented early and with body weight of less than 20 kilogram.